2021
DOI: 10.3389/fonc.2021.594917
|View full text |Cite
|
Sign up to set email alerts
|

Can Nimesulide Nanoparticles Be a Therapeutic Strategy for the Inhibition of the KRAS/PTEN Signaling Pathway in Pancreatic Cancer?

Abstract: Pancreatic cancer is an aggressive, devastating disease due to its invasiveness, rapid progression, and resistance to surgical, pharmacological, chemotherapy, and radiotherapy treatments. The disease develops from PanINs lesions that progress through different stages. KRAS mutations are frequently observed in these lesions, accompanied by inactivation of PTEN, hyperactivation of the PI3K/AKT pathway, and chronic inflammation with overexpression of COX-2. Nimesulide is a selective COX-2 inhibitor that has shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 109 publications
(396 reference statements)
0
2
0
2
Order By: Relevance
“…In this study, agent L1 is found to be soluble in solvents such as methanol, ethanol, DMSO, CHCl 3 , acetone, and water ( Ferreira et al, 2021 ). Agent L1 purity was tested by elemental analysis, FTIR, 1H NMR, and 13C NMR.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, agent L1 is found to be soluble in solvents such as methanol, ethanol, DMSO, CHCl 3 , acetone, and water ( Ferreira et al, 2021 ). Agent L1 purity was tested by elemental analysis, FTIR, 1H NMR, and 13C NMR.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study proposed a formulation encapsulating nimesulide, an NSAID and potential inhibitor of the KRAS/PTEN signaling pathway, in SLNs. This method aims to boost bioavailability, reduce hepatotoxicity, and inhibit cell growth in PanIN cells by increasing PTEN levels [177]. In order to improve the efficacy of the PDAC standard treatment drug gemcitabine, a 2019 study evaluated the impact of a gemcitabine-loaded SLN (Gem-SLN) on MiaPaCa-2 and patient-derived primary pancreatic cancer cell lines (PPCL-46).…”
Section: Solid Lipid Nanoparticlesmentioning
confidence: 99%
“…O nimesulide apresenta efeito supressor nas células cancerígenas e ação antiproliferativa, sendo capaz de estimular apoptose em câncer mamário (FERREIRA et al, 2021). Em estudos com ratas com câncer mamário induzido, Nakatsugi et al (2000) demonstraram que o nimesulide foi capaz de suprimir a evolução da doença, provocando redução no tamanho e na proliferação dos carcinomas.…”
Section: Inibidores Da Cox-2unclassified